Effect of corrosion on the bond behaviour of OPC and PPC concretes - Bhaskar, S.; Bharatkumar, B.H.; Gettu, Ravindra; Neelamegam, M. (Journal of Structural Engineering, 2025)
The phenomenon of reinforcement corrosion and consequent damage to concrete is one of the menacing durability problems in reinforced concrete structures. The objective of the present study is to assess the bond behaviour of concrete subjected to accelerated corrosion test. Based on the experimental results, an empirical bond-slip model is proposed for uncorroded rebars. It is found that the bond behaviour of Portland Pozzolana Cement (PPC) concrete is better than Ordinary Portland Cement (OPC) concrete under corrosion. Therefore, PPC concrete is better for the corrosion inhibition and enhancement of the service life in chloride corrosive environments.